Robotic Single-Site Surgery for Female-to-Male Transsexuals: Preliminary Experience - Stefano Bogliolo; Chiara Cassani; Luciana Babilonti; Barbara Gardella; Francesca Zanellini; Mattia Dominoni; Valentina Santamaria; Rossella Elena Nappi; Arsenio Spinillo (The Scientific World Journal)
Hysterectomy with bilateral salpingo-oophorectomy is a part of gender reassignment surgery for the treatment of female-to-male transsexualism. Over the last years many efforts were made in order to reduce invasiveness of laparoscopic and robotic surgery such as the introduction of single-site approach. We report our preliminary experience on single-site robotic hysterectomy for cross-sex reassignment surgery. Our data suggest that single-site robotic hysterectomy is feasible and safe in female-to-male transsexualism with some benefits in terms of postoperative pain and aesthetic results.